Given i is the imaginary unit, (2- yi)^2 in simplest form is
In order to do this problem, we have to remember just one simple rule: i ^2 = -1
To solve the problem we first can distribute the terms
(2- yi)^2 = (2-yi) (2-yi) = 4 - 2yi - 2yi + (y^2)(i^2 )= 4 - 4yi - y^2
Remember that i^2 = -1 and therefore (y^2)(i^2 ) becomes simply -y^2
Working with imaginary numbers might seem scary at first, but its nothing other than algebra we are already used to with the knowledge that i squared is equal to negative one.
To find an amazing math tutor in NYC or online, please contact us here.